Phytochemical Screening, HPTLC and FT-IR analysis of methanolic bark extract of Syzygium stocksii (Duthie) Gamble – a critically endangered taxon in Myrtaceae - A.E. Johns; P.M. Radhamany (International Journal of Biology and Chemistry, 2024)
Syzygium is a large genus with numerous species in the Family Myrtaceae. The genus Syzygium is a treasure trove of phytochemicals with immene therapeutic potential. Syzygium stocksii (Duthie) Gamble syn. Syzygium travancoricum, a critically endangered plant collected from Thrissur District in Kerala, India. The present study aims at the preliminary phytochemical screening, HPTLC and FT-IR analysis of the plant. Qualitative phytochemical studies revealed the presence of alkaloids, phenolics, flavonoids, tannins, and terpenoids. The preliminary phytochemical screening results revealed the presence of more constituents on the methanolic bark extract, and hence, this was further subjected to an HPTLC analysis to determine the number of compounds in the crude extract. FTIR analysis was also conducted to identify the major functional groups in the compounds in the extract. From this study, it can be concluded that Syzygium stocksii contains various bioactive compounds. This study calls for the importance of excavating the phytochemical and pharmacological potential of this relatively unexplored species.